Linguistic terms and ontological modeling theory - Jo‘rayeva , Oqila Orzi qizi (The Lingua Spectrum, 2026)
This article examines the concept of linguistic terms, their semantic, structural, functional, contextual, semantic, pragmatic, structural, scientific-theoretical, and practical characteristics, as well as their role in the formation of scientific communication and terminological systems. The precision, consistency, coherence, efficiency of terms, their application in scientific and practical domains, methodological approaches in terminological research, theoretical foundations, scientific experience, and practical outcomes are analyzed. The article provides a detailed analysis of the theoretical, methodological, and practical foundations of ontological modeling of linguistic knowledge, the concept of ontology, the essence of linguistic ontology, its structural and functional components, interactive features, and the role of ontology in modeling terminological systems. The study substantiates the relevance of creating an ontological model of linguistic terms in modern linguistics, computational linguistics, and natural language processing (NLP). The conclusions emphasize the scientific, practical, theoretical, and methodological significance of systematic, consistent, and effective modeling of terms.